Negotiating the Space for Peace: Interreligious Tolerance and Harmony in Practice - Rohman, Muhammad Saifullah (Journal of Indonesian Social Sciences and Humanities, 2018)
Nowadays, Indonesia well known as tolerance country has been facing a severe problem with the practice of intolerance act and radicalism. Recently, we were shocked by some news about a young man attacking St. Lidwina Bedog church, Yogyakarta, and the suicide bombing at three churches in Surabaya. Several innocent civilians became the victim from these actions. Besides, we can note that there was another intolerant act regarding the building of a house of worship and conflict among religious believers in some district in Indonesia. These situations indicated that actors who attempted to destroy Indonesia’s unity through harmful narratives of Indonesian diversity and threaten Indonesian tolerance are ranging from ethnicity, language, to religion. This article proposes a counter-narrative for Indonesian harmony by identifying the places of house of worship and spaces of religious tolerance activities. Since the establishments of the house of worship in several places have led to a disharmony and intolerance act, this article found another story of tolerance based on a house of worship location and space of tolerance activity. Field research was conducted in Balun Village, Lamongan, where three houses of worship built neighboring in the village. These neighboring houses of worship and religious activities around support the idea called “negotiating the space of peace.” The data collection methods included participant observation and interview. The findings show that religious diversity of Indonesian citizens is based on unity and peace. The neighboring houses of worships (Mosque, Church, Pura/ Hinduism temple, etc.) in Lamongan, show that the tolerance among different religious believers has been there as long as Indonesian history. It is not only the negotiation in terms of physical space where the house of worship built but also non-physical space among religions and their believers, which build and strengthen the peace among them. Therefore, the peace situation and condition become the central point regardless of their background (ethnicity, religions, and language).